Challenges of Justice in the Context of Plant Genetic Resources - Deplazes-Zemp, Anna (Frontiers in Plant Science, 2019)
In this article I discuss access and benefit-sharing (ABS) for plant genetic resources from an ethical perspective. This leads to the question of what types of justice actually play a role when more equity and fairness is demanded for plant genetic resources. Five dimensions of justice will be distinguished: classical distributive justice, which deals with a fair distribution of goods; commutative justice, which concerns a fair exchange of ‘give-and-receive’; justice as recognition, which relates to treating all involved parties with the same respect; reparative justice, which pertains to fair amendments for wrongful actions in the past; and procedural justice, which is concerned with just decision processes. Drawing on the discussion of ethical problems with biopiracy, the distribution of environmental burdens, and plant genetic resources in agriculture, I will illustrate that the use of genetic resources poses challenges across all five dimensions of justice. Because the combination of justice challenges are specific for each case of resource use, I will argue that it is important that users of genetic resources are aware of the complexity of the justice problems in order to ensure fair and equitable ABS negotiations.